2017
DOI: 10.3732/ajb.1700246
|View full text |Cite
|
Sign up to set email alerts
|

An exquisitely preserved filmy fern (Hymenophyllaceae) from the Early Cretaceous of Mongolia

Abstract: Hymenophyllum iwatsukii was likely an epiphyte based on the sedimentary environment in which the fossils are preserved, the associated fossil flora, and the growth habit of extant species of Hymenophyllum. The new fossil species underlines the extent to which morphological characters in Hymenophyllum have been conserved despite significant tectonic, climatic, ecological, and floristic changes since the Early Cretaceous.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 42 publications
(49 reference statements)
0
21
0
Order By: Relevance
“…They are either epiphytic or terrestrial and predominantly tropical (Kramer and Green 1990). A typical feature giving the common name 'filmy fern' is the membranaceous lamina which lack stomata and has only one cell-layer between the veins (Kramer and Green 1990 (Axsmith et al 2001, Herrera et al 2017. Based on fossilcalibrated molecular dating the origin of filmy fern lineage has been dated at Permian or Carboniferous (Schuettpelz and Pryer 2006, 2009, Testo and Sundue 2016, Lehtonen et al 2017.…”
Section: Introductionmentioning
confidence: 99%
“…They are either epiphytic or terrestrial and predominantly tropical (Kramer and Green 1990). A typical feature giving the common name 'filmy fern' is the membranaceous lamina which lack stomata and has only one cell-layer between the veins (Kramer and Green 1990 (Axsmith et al 2001, Herrera et al 2017. Based on fossilcalibrated molecular dating the origin of filmy fern lineage has been dated at Permian or Carboniferous (Schuettpelz and Pryer 2006, 2009, Testo and Sundue 2016, Lehtonen et al 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Other fossils in the Hymenophyllaceae were reviewed by Herrera et al (2017) when they described Hymenophyllum iwatsukii . We agree with their assessment for the fossils whose placement in the family is questionable due to lack of characteristics for the fossil material.…”
Section: Discussionmentioning
confidence: 99%
“…For all specimens that remain in the family, the sori are located at the margins of the pinnule segments and not next to the costa, as in Acrostichopteris . Often the characters of the sori and sporangia, such as the tubular indusium or the extension of the receptacle that protrudes from the tip of the sorus in Trichomanes , are difficult to distinguish in the fossil material, which can make assignment to genus difficult (Herrera et al, 2017). The oldest known fossil, Hopetedia preatermissa (Axsmith et al, 2001), showed some resemblance to Trichomanes , although Axsmith et al cautioned against assumptions that this is an ancestral form, because the short receptacle appeared to be more derived and is more characteristic of Hymenophyllum and the indusium appears to be bivalvate, as it is in Hymenophyllum (Axsmith et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Growing alongside the Krassilovia plant were a variety of other presumed trees, including taxa related to extant Pinaceae (Schizolepidopsis, Picea, Pityostrobus, [65,86]), Cupressaceae (Elatides, Stutzeliastrobus, Pentakonos, [64,87], and the ginkgophyte Umaltolepis [70], as well as plants that may have been shrubs, such as the corystosperm Umkomasia [31,32]. The absence of lycopods and ferns (as macrofossils, mesofossils, or megaspores), other than the epiphytic filmy fern Hymenophyllum [88], suggests there was little or no herbaceous vegetation. A miniscule moss (Herrera, F. personal observation), represented by only a few fragments in the Tevshiin Govi flora may also have been epiphytic.…”
Section: Paleoecology Of the Krassilovia Mongolica-podozamites Harrismentioning
confidence: 99%